A People for the Patricians: Cuadros De Costumbres and State-Making on the Frontier in Colombia and Venezuela. Issue 1 (2nd January 2019) - Martínez-Pinzón, Felipe
Abstract : This essay argues that the individual nature of the sketch of manners (cuadros de costumbres) imagined, in the midst of post-war politicisation of the popular classes, a dismantling of alliances of class and race to privilege a single possible image of community: the nation. By reconstructing the discourses – in particular of José María Vergara y Vergara and Ramón Páez – that facilitated the production of the llanero type in Venezuela and the Indian (indio) type in Colombia, this essay posits the sketcher as embodying a 'patrician mindset'. As a product of it, the sketchers project their own personal histories onto their representations of the people and, in so doing, erases the frontier histories of these populations. By confounding the history of the nation with their own histories, Vergara y Vergara and Páez equated 'patria' with patrimony, producing peaceful populations as 'pueblo' (national people). Paradoxically, these idyllic portraits of the 'pueblo' belie an all but peaceful principle of authority that these post-independence patricians used to legitimise themselves.